Effects of afforestation on runoff and sediment load in an upland Mediterranean catchment - Buendia, C; Bussi, G; Tuset, J; Vericat, D; Sabater, S; Palau, A; Batalla, R (Elsevier, 2015)
This paper assesses annual and seasonal trends in runoff and sediment load resulting from climate variability and afforestation in an upland Mediterranean basin, the Ribera Salada (NE Iberian Peninsula). We implemented a hydrological and sediment transport distributed model (TETIS) with a daily time-step, using continuous discharge and sediment transport data collected at a monitoring station during the period 2009–2013. Once calibrated and validated, the model was used to simulate the hydrosedimentary response of the basin for the period 1971–2014 using historical climate and land use data. Simulated series were further used to (i) detect sediment transport and hydrologic trends at different temporal scales (annual, seasonal); (ii) assess changes in the contribution of extreme events (i.e. lowand high flows) and (ii) assess the relative effect of forest expansion and climate variability on trends observed by applying a scenario of constant land use. The non-parametric Mann–Kendall test indicated upward trends for temperature and decreasing trends (although non-significant) for precipitation. Downward trends occurred for annual runoff, and less significantly for sediment yield. Reductions in runoff were less intense when afforestation was not considered in the model, while trends in sediment yield were reversed. Results also indicated that an increase in the river's torrential behaviour may have occurred throughout the studied period, with low and high flow events gaining importance with respect to the annual contribution, although its magnitude was reduced over time.